PENILAIAN KUALITAS HIDUP EORTC QLQC30 DAN EORTC QLQBN20 PADA PASIEN TUMOR PRIMER INTRAKRANIAL PASCATERAPI - Ratih Puspa,* Yusuf Wibisono,* Henny Anggraini Sadeli* (NEURONA, 2018)
INTRODUCTION INCREASING NUMBER OF SURVIVING PRIMARY INTRACRANIAL TUMOR PATIENTS IN LINE WITH DISCOVERY OF NEW TREATMENT WILL INCREASE THE PATIENTS MORBIDITYTHIS MAKES QUALITY OF LIFE OF PATIENT NEED TO BE EVALUATED